STATUS HOMOCYSTEINE DAN ASAM FOLAT PADA IBU HAMIL MEREKA - Dewi Permaesih; Yuniar Rosmalina; Reviana Christijani; Muhilal Muhilal (Persagi, 2001)
HOMOCYSTEINE AND FOLIC ACID STATUS OF ANEMIC PREGNANT WOMEN.Background: Folic acid deficiency among pregnant women in Indonesia is quite prevalent. It is believed to cause the anemia and the risk of infant neutral tube defect. Folic acid plays a certain role in homocysteine convertion into methionine. Serum homocysteine will increase with the decrease folic acid.Objective: To obtain folic acid consumption, homocysteine and folic acid status in pregnant women suffering from anemia using recent method of determination, and relationship of the three variables.Methodology: Pregnant women in the study area were screened by their Hb values under 11 g/dL. Thirty anemic pregnant women consumption was obtained by used 2x24 hours recall method. Folic acid was analysed by Ion Capture Method and homocysteine was analysed by Fluoresence Polarization Immuno assay.Results: Folic acid consumption was 61 ± 50 µg/mL with a range of 3.5 to 15.1 µg/mL. Normal value of serum folic acid was 3.1 to 12.4 µg/mL. Therefore, the value folic acid of pregnant women in this study was still in the range of normal value. Serum homocysteine value in pregnant women was 7.1 ± 1.95 µg/mL with a range of 3.0 to 10.9 µg/mL, while normal value was 5 to 15 µg/dL.Conclusion: homocysteine, folic acid, pregnant women, anemia.